A RANDOMIZED COMPARATIVE STUDY OF EARLY AND DELAYED LAPAROSCOPIC CHOLECYSTECTOMY IN ACUTE CHOLECYSTITIS: A TERTIARY CENTER EXPERIENCE AND REVIEW OF LITERATURE - YADAV, RAHUL; RAO, HARSHITA; GOEL, GAURAB (International Journal of Current Pharmaceutical Research, 2023)
Objective: It is established that the standard treatment foracute cholecystitis is laparoscopic cholecystectomy. However, the question of the timing of surgery remains controversial. To compare early laparoscopic cholecystectomies (within 72 h of symptom onset) and delayed laparoscopic cholecystectomies (beyond 72 h) for acute cholecystitis in terms of intra-operative difficulties and post-operative complications. Methods: The patients operated on for acute cholecystitis, between December 2018 and December 2021, were included in a prospective study. They were divided into two groups based on whether surgery was performed before (group 1) or after (group 2) 72 h after the onset of symptoms. We conducted a comparison between the two groups. Results: The two groups were comparable in terms of demographics, clinical presentation, and radiological findings. The duration of surgery was significantly longer for group 2 (53.6 min versus 30.7 min, p<0.001). There was more conversion in group 2 than in group 1, without a significant difference (6% versus 0%, p = 0.17). There were no postoperative deaths during the study period. Specific post-operative complications were comparable between the two groups. The post-operative hospital stay was significantly longer in group 2 (9.3 d versus 5.4 d) Conclusion: In the case of acute cholecystitis, early surgery can reduce the cost of care, the duration of surgery and the hospital stay while the conversion rate and postoperative morbidity are comparable to the delayed treatment.